Desmopressin acetate decreases blood loss in patients with massive hemorrhage undergoing gastrointestinal surgery - Wang, Li-Chun; Hu, Ying-Fang; Chen, Lei; Xing, Rui; Lin, Xin-Feng; Kou, Qiu-Ye (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Intraoperative blood loss more than 400 mL during gastrointestinal surgery is an independent predictor of mortality. Desmopressin acetate (DDAVP) could reduce perioperative blood loss. Few studies have prompted concerning the effects of DDAVP on gastrointestinal surgery. This study was to investigate whether DDAVP can decrease blood loss in patients with massive hemorrhage undergoing gastrointestinal surgery. Materials and Methods: A multiple-centers, double-blind clinical trial was conducted, patients who underwent gastrointestinal surgery were recruited from 3 hospitals, randomly assigned to two different groups. Patients in the treatment group received desmopressin 0.3 ug/kg,30 min once a day after surgery, patients in the control group received 50 ml saline for 30 min. The primary outcome was the changes of hemoglobin at 24 hours after the surgery. And the secondary outcomes included coagulation function, urine volume, serum creatinine, and safety. Results: There were 59 patients enrolled between 1 June 2015 and 1 June 2017. At 24hr.after surgery, a decrease in hemoglobin in the DDAVP group was significantly lower than that in the NS group (-5.0±6.9 g/L vs. -10.2±9.3g/L, p=0.03). Sonoclot® showed that the platelet function in the DDAVP group was higher than that in NS group at 24 hr. (2.56 ±0.59 vs. 1.91 ±0.72, p<0.05). There was no difference in urine volume and serum creatinine at 24 hr. between two group. Conclusion: DDAVP could reduce post-operation blood loss in patients with massive hemorrhage undergoing surgery by improving the platelet function. We observed no difference in urine volume and serum creatinine in two groups.